2014
DOI: 10.1007/s11869-014-0275-6
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of travel activity and urbanicity on exposures to ambient oxides of nitrogen and on exposure disparities

Abstract: Daily exposures to ambient oxides of nitrogen were estimated here for residents of Hillsborough County, FL. The 2009 National Household Travel Survey provided geocoded data on fixed activity locations during each person-day sampled. Routes between activity locations were calculated from transportation network data, assuming the quickest travel path. To estimate daily exposure concentrations for each person-day, the exposure locations were matched with diurnally and spatially varying ambient pollutant concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 71 publications
4
17
0
Order By: Relevance
“…The best of these performed fairly well against results from personal passive samplers (r=0.60-0.62). Further research in Hillsborough County, FL, USA, utilizing data generated by the CALPUFF dispersion model, eventuated in an urban residential group mean exposure of 22 μg/m 3 and individual exposures up to 43 μg/m 3 (Gurram et al 2014). The collective results from these NO x studies are reasonably comparable to our group means of 25-60 μg/m 3 (Table 2, Appendix 7).…”
Section: Recent Exposure Modeling Studiessupporting
confidence: 71%
See 1 more Smart Citation
“…The best of these performed fairly well against results from personal passive samplers (r=0.60-0.62). Further research in Hillsborough County, FL, USA, utilizing data generated by the CALPUFF dispersion model, eventuated in an urban residential group mean exposure of 22 μg/m 3 and individual exposures up to 43 μg/m 3 (Gurram et al 2014). The collective results from these NO x studies are reasonably comparable to our group means of 25-60 μg/m 3 (Table 2, Appendix 7).…”
Section: Recent Exposure Modeling Studiessupporting
confidence: 71%
“…Despite all of the limitations mentioned herein, our results do not deviate wildly from the ranges found in previous modeling studies (Gurram et al 2014;Hannam et al 2013;Zidek et al 2005). Finally, a larger population sample would have likely strengthened statistical associations between occupational groups at the interaction effect level and improved estimates of potential exposure benefits when moving further away from the highway.…”
Section: Study Limitations and Recommendationssupporting
confidence: 51%
“…A significant body of international quantitative Environmental Justice research has found that vulnerable subpopulations-particularly low-income communities and ethnic minorities-are exposed to higher concentrations of air pollution compared to the rest of the population (Chakraborty et al 2011, Taylor 2011, Hajat et al 2015, Holifield et al 2017. A small number of studies have examined age as well, with some evidence of disparities in exposure to air pollution between age groups, although these findings are not consistent across studies (Clark et al 2014, Gurram et al 2015, Clark et al 2017, Gurram et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…These make it an interesting test case from an air pollution perspective. Source: Gurram et al (2015) 90.3 Modeling Framework Figure 90.2 depicts the modeling framework used to simulate urban population activity and transportation network performance for the study region. An activity-based model (ABM) of travel demand (DaySim) is coupled with MATSim, here applied as a dynamic tra c assignment (DTA) model.…”
Section: Study Areamentioning
confidence: 99%
“…The resulting pollutant concentrations will be combined with the diurnal locations of individuals (obtained from the ABM and MATSim) to estimate individual-level exposure to tra c-related pollutants, such as nitrogen oxides. Such individual-level exposure measures will be utilized to estimate demographic group-level exposures for assessment of inequality in exposure to tra c-related air pollution, as we have done previously using travel survey data (Gurram et al, 2015). The model system described above will be used to obtain estimates of population exposure, for alternative scenarios of urban land-use design and transport policies.…”
Section: Future Workmentioning
confidence: 99%